2020
DOI: 10.1002/anie.201914747
|View full text |Cite
|
Sign up to set email alerts
|

Access to Hydroxy‐Functionalized Polypropylene through Coordination Polymerization

Abstract: Preparation of polyethylenes containing hydroxy groups has been already industrialized through radical copolymerization under harsh conditions followed by alcoholysis. By contrast, hydroxy‐functionalized polypropylene has proven a rather challenging goal in polymer science. Propylene can't be polymerized through a radical mechanism, and its coordination copolymerization with polar monomers is frustrated by catalyst poisoning. Herein, we report a new strategy to reach this target. The coordination polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Thus, highly 1,2‐selective polymerization of allene monomers is rare. Cui's group did a milestone work of 1,2‐selective polymerization of polar and nonpolar alkylallene monomers with rare‐earth‐metal catalytic systems [13] . The 1,2‐selectivity of the allene polymerization could be over 99%.…”
Section: Preparation Of Polyallenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, highly 1,2‐selective polymerization of allene monomers is rare. Cui's group did a milestone work of 1,2‐selective polymerization of polar and nonpolar alkylallene monomers with rare‐earth‐metal catalytic systems [13] . The 1,2‐selectivity of the allene polymerization could be over 99%.…”
Section: Preparation Of Polyallenesmentioning
confidence: 99%
“…In addition, helix‐sense selective polymerization (HSSP) of achiral allene monomers with chiral catalysts to afford helical polyallenes has also been reported [12] . What's more, polyallenes with excellent 1,2 or 2,3‐regularity have been synthesized [13–15] …”
Section: Introductionmentioning
confidence: 99%
“…24 Then, the stereoselective (co)polymerization of a series of unprotected polar monomers using a rare earth catalyst to afford stereoregular and sequence-controlled polymers was reported by this group. [25][26][27][28][29][30][31][32][33][34][35][36] Our group shown that rare earth catalysts can be used for the stereoselective polymerization of polar 2-vinylpyriding (2-VP). The coordination of a nitrogen atom as well as an olefin CvC bond to the metal center was essential to achieve reactivity and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This spurs researchers to develop various ways to protect the active species, such as using bulky substituents to mask the polar groups, precomplexing the polar groups with alkylaluminum, and separating the polar groups from the polymerizable units by a long spacer and so on. However, for early transition metal complexes with highly oxyphilic metal centers, it is also a challenge to realize the polymerization of polar monomers. Interestingly, a family of rare-earth catalysts was recently reported to successfully promote the polymerization of polar monomers, , and in some cases the polar group can inconceivably activate the polymerization but not poison the metal centers . Cui and co-workers reported that the polymerization of polar ortho -methoxystyrene ( o MOS) could be achieved by cationic β-diketiminato rare earth-metal species to produce isoselective polymers.…”
Section: Introductionmentioning
confidence: 99%